Differential growth and yield by canola (Brassica napus L.) and wheat (Triticum aestivum L.) arising from alterations in chemical properties of sandy soils due to additions of fly ash. (15th October 2012) - Yunusa, Isa A M; Manoharan, Veeragathipillai; Harris, Rob; Lawrie, Roy; Pal, Yash; Quiton, Jonathan T; Bell, Richard; Eamus, Derek
Abstract Background There is a need for field trials on testing agronomic potential of coal fly ash to engender routine use of this technology. Two field trials were undertaken with alkaline and acidic fly ashes supplied at between 3 and 6 Mg ha−1 to acidic soils and sown to wheat and canola at Richmond (Eastern Australia) and to wheat only at Merredin (Western Australia). Results Ash addition marginally (P< 0.10) raised the pH in the top soil layers at both sites. The exceptionally dry season at both sites constrained yields and thwarted any likelihood of gaining yield benefits from ash‐induced improvements in soil conditions. Yield improvements due to ash addition were absent at Merredin and only marginal at Richmond, where no elevated accumulation of B, Mo, Se, P or S in either the straw or seeds of wheat was observed; canola increased accumulation of Mo and Se in its shoot with acidic fly ash, but it was well below phyto toxic levels. Simulations of wheat using APSIM at Richmond over a 100‐year period (1909–2008) predicted yield increases in 52% of years with addition of ash at 3.0 Mg ha−1 compared with 24% of years with addition of ash at 6.0 Mg ha−1. The simulated yield increases did not exceed 40% over the control with addition of 6 Mg ha−1 ash, but was between 40% and 50% with an addition rate of 3 Mg ha−1. Conclusion We found no evidence of phytotoxicity in either crop in this unusually dry year and there is still a need for further field assessment in years with favourable rainfall to enable development of clear recommendations on fly ash rates for optimum yield benefits.© 2012 Society of Chemical Industry